(3eSCdI JVYja GdePHMs - (3GdMdHj, EHQGgje Hf eMeO EHQGgje, J (B956 (3g`s
(3ChdgG (B:s
(3fMcOc jG ef JOdgJ HHGgQ LdGdg YhGde GdedchJ deG QCjJ eSCdI JVYja GdePHM GdePchQI aj TQM OjhGf CejQ GdeDefjf Ydj Hf CHj WGdH cQe Gddg JYGdi hLgg ddeMbb GdeHjOj GdTgjQ HbGVj ejQ s
(3BNQgG (B:s
(3hjfSHhf Edi MVQI CejQ GdeDefjf Ydj Hf CHj WGdH cQe Gddg JYGdi hLgg Cfg cGf jbhd SHMGf ef dG jYde LPQ GdYTQI EdG gh hMGT ddg Cf jchf HGH eOjfI GdYde ef jNai Ydjg eKd Pdc Jes
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdQjGVjGJs